PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) DALAM MENINGKATKAN KEAKTIFAN SISWA - Puji Utami, Riani (Universitas Palangka Raya, 2022)
The purpose of this study was to increase student activity by implementing a project based learning (PjBL) model at SMA Bina Insani Bogor. This research is an action research of Guidance Counseling (PTBK) class which is conducted in one cycle consisting of one meeting. The research sample was students of class X Mipa 1 odd semester in the 2021-2022 academic year at SMA Bina Insani Bogor with a total of 21 students. The results of this study indicate that student learning activity has increased in learning in cycle I. The increase in student activity occurs because in learning by applying the Project Based Learning model students are active by discussing each group that has been divided to observe problems in adolescent development that occur in the surrounding environment. students, compose and complete project assignments with their groups, present the results of the discussions and write the results of group discussions in the Dream Book. This shows that the Project Based Learning learning model can increase student activity in observing adolescent problems.